The Union assaults at Vicksburg : Grant attacks Pemberton, May 17-22, 1863 - Smith, Timothy B., 1974- (Modern war studies., 2020)
"The Vicksburg Campaign is one of the Civil War's most important operations and one that solidified Ulysses S. Grant's position as one of the most significant military commanders in history. It was a series of battles and maneuvers against the last section of the Mississippi River controlled by the Confederacy and thus was critical to the Union's success. While the overall campaign has had numerous examinations by prominent historians, studies of the individual battles that made up the campaign have been much more sporadic, with only Smith's Champion Hill (Savas Beatie, 2004) examining any of the engagements in depth. "Gallant in the Extreme" examines the assaults on Vicksburg in May of 1863 that led eventually to the Confederacy's surrender in July"--